Answer:
Step-by-step explanation:
x³-6x²+11x-6
put x=1
1³-6×1²+11×1-6=1-6=11-6=0
by synthetic division
1| 1 -6 11 -6
| 1 -5 6
|----------------
| 1 -5 6 |0
x²-5x+6=0
x²-2x-3x+6=0
x(x-2)-3(x-2)=0
(x-2)(x-3)=0
x=1
x-1=0
so x³-6x²+11x-6=(x-1)(x-2)(x-3)
For example: if the word problem were simply "4 divided by 2", the fraction would be a 4 with a line underneath and the 2 underneath that.
I hope I made this possible to understand... let me know if you were referring to something else!
Answer:
the true answer is 9
Step-by-step explanation:
Because the product of the absolute value is the same number and positive
Answer:
yes
Step-by-step explanation:
Answer:
around 917
Step-by-step explanation: